Experimental study on a Nb3Al insert coil under high magnetic field. (June 2016) - Zhu, Guang; Dai, Yinming; Cheng, Junsheng; Chang, Kun; Liu, Jianhua; Wang, Qiuliang; Pan, Xifeng; Li, Chao
Highlights: It is a new attempt for developing Nb3 Al magnet technics. The experimental magnet was test in 7–15 T field. And the performance of the magnet was analyzed. The new technics in magnet manufacture were introduced. Abstract: Nb3 Al is one of the most promising superconductors to replace Nb3 Sn in large scale, high field superconducting magnet. Since the complicated conductor manufacturing process, long and stable Nb3 Al conductor is difficult to acquire in a commercial scale. Based on a 70 m length of Nb–Al precursor conductor, we designed and fabricated a Nb3 Al coil. The coil winding, low temperature diffusion heat treatment and epoxy impregnation are described in detail. The finished Nb3 Al coil is tested as an insert in a background magnet. The test is performed at the background field from 7 T to 15 T. The test results are analyzed and presented in this paper.